The politics of language and education in Georgia (compared with the Baltic States and Ukraine) - Dundua, Salome (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2014)
In the process of ensuring successful and full integration, one of the main obstacles is the lack of knowledge of the state language by ethnic minorities. Despite the fact that Georgia has achieved some success in building a democratic state, democratic institutions are still weak in the country. Having weak democratic institutions makes it very difficult to transform diverse religious and ethnic groups into one civil unit. A lack of trust towards political institutions on the one hand, and the weakness of these institutions on the other, leads to the mutual alienation and isolation of different segments of society. The Georgian government, unlike the Baltic States and Ukraine, by way of teaching Georgian to its minorities, set increasing their civic integration and activity in civic spaces as a goal. How successful the steps taken in this regard were is another question.

W procesie zapewniania pełnej integracji mniejszości narodowych w państwie, jedną z najczęściej wymienianych przeszkód jest brak znajomości języka państwowego przez owe mniejszości. Pomimo faktu, że Gruzja osiągnęła pewien sukces w budowaniu demokracji, instytucje państwowe są wciąż słabe, co z kolei przekłada się na trudności w procesie integrowania różnych grup religijnych i etnicznych z państwem. Brak zaufania do instytucji politycznych z jednej strony i słabość tych instytucji z drugiej, prowadzi do wzajemnego wyobcowania i izolacji różnych grup społecznych. Rząd gruziński, w przeciwieństwie do krajów bałtyckich i Ukrainy, zbliżając Gruzinów do tamtejszych grup mniejszościowych, postanowią zwiększyć ich udział i aktywność w przestrzeni obywatelskiej.
Polityka językowa i edukacyjna w Gruzji (analiza porównawcza: Gruzja, kraje bałtyckie i Ukraina)
Keywords: ethnic minorities; education; language politics; integration; mniejszości etniczne; edukacja; polityka językowa; integracja